2014
DOI: 10.1091/mbc.e14-06-1169
|View full text |Cite
|
Sign up to set email alerts
|

The GolgiS-acylation machinery comprises zDHHC enzymes with major differences in substrate affinity andS-acylation activity

Abstract: The molecular machinery that catalyzes S-acylation reactions at the Golgi comprises zDHHC enzymes with major differences in substrate affinity and S-acylation activity. It is proposed that the coexistence of these two groups of enzymes in cells is important to allow the Golgi S-acylation machinery to modify a wide and diverse set of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 35 publications
4
111
1
Order By: Relevance
“…The synaptosomal protein Snap25b is a major target of DHHC17 (as well as other DHHCs), with the palmitoylation of the four cysteines being necessary for the proper targeting of Snap25b to the presynaptic membrane and subsequent assembly of the SNARE complex (Gonzalo and Linder, 1998). Moreover, the recently discovered substrate recognition motif of Snap25b is necessary and sufficient for DHHC17-Snap25b interactions (Lemonidis et al, 2014). The objective of the present work was to determine the structural and biophysical underpinnings of the interaction between ANK17 and Snap25b and extend the results to Huntingtin, another substrate of DHHC17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synaptosomal protein Snap25b is a major target of DHHC17 (as well as other DHHCs), with the palmitoylation of the four cysteines being necessary for the proper targeting of Snap25b to the presynaptic membrane and subsequent assembly of the SNARE complex (Gonzalo and Linder, 1998). Moreover, the recently discovered substrate recognition motif of Snap25b is necessary and sufficient for DHHC17-Snap25b interactions (Lemonidis et al, 2014). The objective of the present work was to determine the structural and biophysical underpinnings of the interaction between ANK17 and Snap25b and extend the results to Huntingtin, another substrate of DHHC17.…”
Section: Discussionmentioning
confidence: 99%
“…(Sanders et al, 2015). Recently, Chamberlain and colleagues showed that the cytoplasmic domain of DHHC17 is both necessary and sufficient to bind Snap25b (Synaptosomal-associated protein 25) (Lemonidis et al, 2014). They used alanine scanning mutagenesis and bioinformatics to identify the sequence motif ΨβXXQP (where Ψ = Val, Ile, Ala or Pro β = Val, Ile or Thr X − X = any two residues , Q = Gln, P = Pro) in SNAP25b and other substrates of DHHC17 that is a critical determinant for substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine residues that lie near the catalytic DHHC motif coordinate two structural zinc atoms that are essential for proper enzyme folding and function, but do not play a catalytic role in palmitate transfer . Despite overall amino acid similarity, the 23 human ZDHHC enzymes exhibit distinct abilities to autoacylate, implying differences in catalytic efficiency . Of note, while often referred to in general as “palmitoylation”, this process can involve not only the addition of palmitate (C16:0), but also other fatty acids with different chain lengths (e.g., C18:0, stearoylation) .…”
Section: Protein S‐palmitoylation: Basic Biochemical Mechanismsmentioning
confidence: 99%
“…For other proteins, palmitoylation requires an initial lipidation event (e.g., RAS C‐terminal farnesylation, SRC‐family N‐terminal myristoylation) at an amino acid residue near the to‐be palmitoylated Cys residue(s), which likely helps localize the substrate to ZDHHC‐enriched membranes (e.g., the Golgi) . Two ZDHHC enzymes, ZDHHC13 and ZDHHC17, contain unique C‐terminal ankyrin‐repeat domains that can bind certain proteins and enhance their membrane localization, facilitating palmitoylation by other ZDHHC enzymes . Efficient palmitoylation by some DHHC enzymes (Erf2/ZDHHC9, ZDHHC6) requires an accessory protein (Erf4/GOLGA7, SELENOK), and speculatively, these accessory proteins could aid in substrate selection .…”
Section: Protein S‐palmitoylation: Basic Biochemical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation